Study of Thermal Neutron Flux and Generated Energy from Linac using CR-39 Detector in Liquid Medium - Kurnia Nur Widyanti; Chomsin S. Widodo; Bunawas Bunawas (Natural B, Journal of Health and Environmental Sciences, 2018)
Linac surgery is required in radiotherapy activities. However, if Linac operated more than 8 MV can cause additional radiation of neutrons, as well as triggers forming secondary cancer. The study was conducted to determine the distribution of thermal neutron flux and energy responses on the trace. One method to detect neutrons is to use a nuclear trace detector. Measurements were made using a CR-39 detector coated with a Boron radiator. A number of detectors were placed on the surface of the sphere and entered into a 30×30×30 cm3 fantom. Irradiation is done by placing fantom under Linac gantry with 100cm SSD distance. After irradiation, then etching. The results of the measurements showed that the distribution of thermal neutron fluxes spread in all directions. Linac 10 MV neutron flux value varies, starting at 0° of 1,637×103 n/cm2.s and decrease at 135°of 1.285×103 n/cm2s. The highest Linac 15 MV at detector position 0° of 10.723x104 n/cm2.s and decreased at 135° of 5.142x104 n/cm2s. This proves that the farther from the source the less the thermal neutron flux value due to the collision process. While Linac 10 MV and 15 MV produce range of diameter ranging from 8.21-16.75 (μm) and 9.21-17.45 (μm), with energy response value 0.5-3.5 MeV. The larger the energy response, the smaller the diameter and vice versa, this is due to the effect of penetration on the depth of the distance resulting in smaller track.